AV.UR.NAVS - Avis urgent aux navigateurs : Post-Diplôme 1993-1994. (Nantes : Ecole Régionale des Beaux-Arts de Nantes, 1994)
Caurant, Philippe ; Crovi, Marjorie ; Dupont, Céline ; Martin, Jean-Philippe ; Lopez, Gilles ; Pellerin, Josée ; Engramer, Sammy ; Harang, Catherine ; Huber, Angelica ; Peinado, Bruno
AV.UR.NAVS - Avis urgent aux navigateurs : Post-Diplôme 1993-1994, Ecole Régionale des Beaux-Arts de Nantes, 17.05 - 02.06.1994
boek